Scary stories to tell in the dark eaudiobook Three books to chill your bones. - Schwartz, Alvin (Scary Stories to Tell in the Dark, 2020)
The complete iconic anthology series of horror tales that's now a feature film! Narrated by Patton Oswalt, Melissa McBride, and Alex Brightman, this collection includes all three of Alvin Schwartz's classic story collections: Scary Stories to Tell in the Dark, More Scary Stories to Tell in the Dark, and Scary Stories 3. Walking corpses, dancing bones, knife-wielding madmen, and narrow escapes from death—they're all here in this chilling collection of ghost stories, collected and retold by folklorist Alvin Schwartz. These horrific tales are guaranteed to raise goosebumps. Let the faint of heart beware. Pull up a chair, find a hand to hold, and prepare to be horrified. Supplemental enhancement PDF accompanies the audiobook.